2021
DOI: 10.1002/jmri.28002
|View full text |Cite
|
Sign up to set email alerts
|

Ex‐VivoMRI of the Normal Human Placenta: Structural–Functional Interplay and the Association With Birth Weight

Abstract: Background Advanced magnetic resonance imaging (MRI) methods are increasingly being used to assess the human placenta. Yet, the structure–function interplay in normal placentas and their associations with pregnancy risks are not fully understood. Purpose To characterize the normal human placental structure (volume and umbilical cord centricity index (CI)) and function (perfusion) ex‐vivo using MRI, to assess their association with birth weight (BW), and identify imaging‐markers for placentas at risk for dysfun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In this context, MRI has recently been employed for FGR fetal and placenta tissue characterization, 18,[31][32][33] placental oxygen levels, 33 and placental and fetus structural and volumetric measurements. 31,32,34,35 Himoto et al demonstrated that placental T 2 values and size were lower in FGR neonates with unfavorable outcomes, and that radiologist placental qualitative evaluation differed between neonates with favorable and unfavorable outcomes. 31 Among the participants, fetuses with lower FBVR had higher rates of interventions for NRFS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, MRI has recently been employed for FGR fetal and placenta tissue characterization, 18,[31][32][33] placental oxygen levels, 33 and placental and fetus structural and volumetric measurements. 31,32,34,35 Himoto et al demonstrated that placental T 2 values and size were lower in FGR neonates with unfavorable outcomes, and that radiologist placental qualitative evaluation differed between neonates with favorable and unfavorable outcomes. 31 Among the participants, fetuses with lower FBVR had higher rates of interventions for NRFS.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a scarcity of data linking MRI features to FGR outcomes, 31 and MRI anthropometric measurements' role in risk stratification has not been explored yet. In this context, MRI has recently been employed for FGR fetal and placenta tissue characterization, 18,31–33 placental oxygen levels, 33 and placental and fetus structural and volumetric measurements 31,32,34,35 . Himoto et al demonstrated that placental T 2 values and size were lower in FGR neonates with unfavorable outcomes, and that radiologist placental qualitative evaluation differed between neonates with favorable and unfavorable outcomes 31 …”
Section: Discussionmentioning
confidence: 99%
“…“Ex vivo MRI of the normal human placenta: structural‐functional interplay and the association with birth weight,” 10 is an ex vivo 3 T MRI study of 13 normal‐term placentas. Placentas were maintained on a perfusion system that mimics fetal placental flow via the umbilical arteries.…”
mentioning
confidence: 99%